Paradigma Islam Transformatif Rekonstruksi Pembaruan Islam Indonesia Dekade 70an Hingga 90an - Halid, Halid (Buletin Al-Turas, 2005)
The term transformation referred to the change that happened in society. Those changes could be viewed from the perception believed by someone o as a stimulant for the alternative paradigm existence. They could also be dividedÂ into three folds: such as conventional, accommodational, and radical.